‘Is This a Hate Speech?’: the Difficulty in Combating Radicalisation in Coded Communications on Social media Platforms - Farrand, Benjamin (European journal on criminal policy and research, 2023)
The use of the Internet for the purposes of radicalisation is well understood. The use of social media platforms to spread messages of hate and intolerance has become mainstreamed, both as a means of communication and a focus of academic attention. The purpose of this paper is to focus on the complications in addressing these radicalisation efforts where the means of communication is through Internet memes, in which humour and coded language are used as means of radicalising an audience. While existing legal frameworks provide for online platforms to tackle this problem through a combination of assuring immunity from liability for taking action when content is brought to a platforms attention, as well as engaging in voluntary proactive measures, this paper explores the difficulty of addressing content that is more borderline in nature and where arguments concerning humour and freedom of expression may be raised by those spreading these messages in a system providing for significant discretion on the part of online platforms. Considering developments under the Digital Services Act, and an increased focusing on the algorithmic control of content, this article will argue that even these new measures may find the countering of radicalising content conveyed through humour quite difficult.